THE INFLUENCE OF THE GROWTH STIMULATOR CHLORELLA ON THE YIELD OF CORN HYBRIDS GROWN IN THE BAZAR-KORGON REGION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
In today’s climate-change-driven climate and agricultural intensification, the use of environmentally friendly methods to increase crop productivity is becoming increasingly important. One promising approach is the use of natural biostimulants.This article presents the results of a study of the effect of a Chlorella vulgaris microalgae suspension on the growth and development of corn (Zea mays L.) in the agroecological conditions of the Bazar-Korgan district of the Jalal-Abad region.The morphophysiological parameters of corn were studied using various Chlorella treatment methods and concentrations. It was determined that the use of Chlorella improves growth, increases photosynthetic activity, and increases corn yield.To achieve a new level of greening agricultural production with minimal man-made pollution, it is necessary to develop new alternative farming systems. Among these, the use of liquid growth stimulants based on chlorella, biostimulants, and fertilizers plays an important role.
Keywords: chlorella, growth stimulants, microalgae, corn, hybrids, yield